Last chance to get it right! : - Moore, J. Thomas (John Wiley & Sons, Inc., 2004)
Praise for Last Chance to Get It Right! "Tom Moore is one of the capable professionals who made me look good in the last thirty years of my forty-five year career at A.G. Edwards & Sons. He has put together a primer which should help both new and veteran investors understand financial markets and alternatives, and gain a direction and common-sense approach to their estate planning." -Benjamin F. Edwards III, Chairman Emeritus A. G. Edwards & Sons "Tom Moore's grasp of the problems of retirement planning is superb; his methods of solving those problems unrivalled." -Richard Austin, past president of Templeton Funds Annuity Company currently a Retirement Income Planning Consultant "Tom has spelled out in plain English, just what it takes to create and implement a successful retirement plan. Boomers and non-boomers alike, will find his step-by-step road map very helpful." -M. Ellen Simmons, JD, CPA Between Social Security uncertainty and uneasiness in the stock market, Americans today face a more uncertain financial future than at any time in decades. Ironically, our response to this growing emergency is to spend more, save less, and put off necessary preparations until tomorrow.